NICC - null (IEE Colloquium on How to Compete and Connect: Understanding the Engineering of Telecommunications Network Interconnection, 1997)
Background Intensive care nursing is a highly demanding field with significant emotional and organisational challenges, yet there is limited understanding of how these factors influence its perceived attractiveness and nurses' retention. Aims This study aimed to explore intensive care nurses' perceptions of the factors influencing the attractiveness of intensive care nursing, the experiences shaping these perceptions and the psychological implications of these factors on their well-being. Study design This descriptive qualitative study included 15 nurses who had been working in an intensive care unit for at least 6 months. Data were collected through semi-structured individual interviews and analysed using thematic analysis. Findings Four main themes were identified as follows: (1) factors enhancing attractiveness, (2) factors reducing attractiveness and weakening retention, (3) psychological effects and coping processes and (4) professional sustainability and retention. Professional development opportunities, meaningfulness of care and team support strengthened professional commitment, whereas excessive workload, unfavourable working conditions and inadequate organisational support weakened it. Burnout, anxiety and moral distress were common psychological experiences. In contrast, organisational support, fair management practices and opportunities for professional development were found to enhance resilience and retention. Conclusion Improving the sustainability of intensive care nursing requires not only supporting individual motivation but also strengthening organisational support mechanisms, expanding psychosocial support services and enhancing opportunities for professional development. Relevance to clinical practice Identifying the factors influencing the attractiveness of intensive care nursing can inform targeted organisational and managerial strategies to improve nurse retention, support psychological well-being and enhance the quality of patient care.